Movimento estudantil em Goiás em tempos de ditadura (1964 1979) - Pereira, Geziel Alves (2015)
This dissertation with the title of the student movement in Goiás in times of dictatorship (1964-1979), was developed in order to rebuild and make reflections on the subject; which has been researched and analyzed, from documents, the archives of the Pontifical Catholic University (PUC-GO), Universidade Federal de Goiás (UFG), periodicals, newspapers, magazines and bibliographies on the subject. Also used depositions (interviews) with ex-militants. The research demonstrated that the vehement student participation, in the period of dictatorship in the context in which they were used, mediated political control, applied by the military of the time; reveals a crisis during the period studied, which led students to the street to express their rights, on behalf of the University and freedom of expression. Students sought strategies for their actions, using rallies, cultural resources, production of plays, songs in protests against the political forces of the time, making the Brazilian company that Brazil is of Brazilians, and not; from the military. The University student movement Ganesan brings approaches that allow the participation of University students in the political process of Goiás, consolidation of democratic institutions in Brazil.